Emerging directions in doctoral education - Blessinger, Patrick; Stockley, Denise (Emerald, 2016)
This volume examines how universities and colleges around the world are developing innovative ways to provide doctoral education, including new theories and models of doctoral education and the impact of changes in government and/or accreditation policy on practices in doctoral education.
Keywords: Education -- Higher.; Universities.; Universities and colleges -- Graduate work.; Doctoral students -- Education.; elektronické knihy; electronic books